The trend of unemployment and crime index during COVID-19 pandemic in Malaysia - Nor Hidayah, Harun (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2023)
Link to publisher's homepage at https://ijbt.unimap.edu.my